The Role of Artificial Intelligence in the Development of 3D Facial Reconstructions on Skull Bones as a Forensic Investigation Solution - Alvina Setiawardania; Ateeq Ur Rahman; Anisa Nadila Utama; Juni Sungsang Prakosa; Yuwono Ariyanto Susilo (Jurnal Indonesia Sosial Teknologi, 2025)
Forensic cases often provide challenges to forensic researchers in conducting investigations, one of which is to identify the body. As technology develops and the digital era, the use of AI technology can also be applied to forensic cases. One of them is in performing facial reconstruction using Artificial Intelligence technology, such as Convolutional Neural Networks (CNN), and Three Dimensional Deep Learning (TDD). The three main components used are 1) Tissue Depth Distribution (TDD), (2) Initial Face Generation, and (3) Anatomy-Guided Face Adaptation. This technique combines biological profiles and performs tissue depth distribution analysis so that it can produce accurate facial reconstructions.